Efficiency coefficient calculation for technical information security based on its parameters - Журиленко, Борис Евгеньевич; Николаева, Надежда Константиновна (Ukrainian Scientific Journal of Information Security, 2015)
This paper shows ways to determine the efficiency coefficient for technical information security in the design stage and analysis of the functioning of technical security. The complexity of the determination of efficiency coefficient for technical information security is the lack of all necessary initial parameters. Therefore, we considered three main options. First, when we know the financial costs invested in the protection and time of the attempt to hacking attempts. The second option – it is when we know the financial costs of the defense and the possibility of breaking the technical security on the first try, which is known for. The probability of breaking proofing for the initial conditions can be calculated using various other existing methods and methods for assessing the quality of technical information security. The third option – the most common, where known, any two attempts, time of break-in attempts and the likelihood of hacking attempts. As a result of research we obtained formulas that allow for these known parameters to build a surface highs probability of breaking technical information security, which can determine the parameters of a possible burglary technical information security for all processes of breaking.